The Adverb in The Speech Of Children From 2 To 6 Years Of Age - Murillo Rojas, Marielos (2020)
The present article aims to contribute with new data about the characterization of the speech of Costa Rican children from 2 to 6 years old, by the description of the function and meaning of the adverbs and the adverbial locutions, used in oral narrations. From the methodological point of view, the presentation of the data follows, roughly, the adverbial classification of Seco (1975), who distinguishes qualifying and determinative adverbs; this decision is based on the possibility of comparing our data with that of Aguado Alonso (2000), the author who opted for the same analysis criteria. As general results, the sample presents 63,70 % or pronominal adverbs and 36,29 % of nominal adverbs. Based on these data, the adverb's acquisition processes are explained in detail.